A Novel Class F Fly Ash-Based Geopolymer and Its Application in Coal Mine Grouting - Luchang Xiong; Zhijun Wan; Shubing Qin; Peng Shi; Junhui Wang; Zhaopeng Wu (Advances in Civil Engineering)
The novel class F fly ash-based geopolymer, largely made of fly ash from the coal solid waste, was used as a kind of grouting material in the coal and electricity-integrated mine from which the solid waste comes, for the purpose of in situ utilization of fly ash. The ratio experiment of material, designed through the orthogonal method, was used to study material properties such as fluidity and strength which are important to the application of mine grouting, and the optimal material proportioning scheme for Green Fly Ash-based grouting material is determined. It has been found out that there was serious rib spalling, roof deformation, obvious floor heave, crack development, and some water seepage in the permanent refuge chamber of the mine. Therefore, to solve these problems, a specific scheme of grouting reinforcement for the surrounding rocks of the permanent refuge chamber and roadway in this mine was designed. Through an analysis of the reinforcement effect of the cementation of surrounding rock after the grouting process, it can be concluded that the green fly ash-based polymer as grouting material can well penetrate into the cracks of the broken surrounding rock and get fully cemented with the surrounding rock and that it can reduce the deformation of the surrounding rock effectively, increase the integrity, and improve the carrying capacity of the surrounding rock. Besides, the grouting reinforcement effect of surrounding rock was verified through numerical simulation, and the grouting process design of green fly ash-based polymer mine was discussed. This study can provide a green and economical approach to the in situ utilization of fly ash which is a kind of coal solid waste.